STRATEGI KOMUNIKASI INTERPERSONAL FRONTLINER DALAM MELAYANI CALON JEMAAH HAJI DI KANTOR KEMENTERIAN AGAMA KOTA MADIUN - Habieb Surya Prayogi (Universitas Merdeka Madiun, 2022)
Abstract— This study aims to determine the Frontliner Interpersonal Communication Strategy in the Service of Prospective Hajj Pilgrims at the Office of the Ministry of Religion Affairs of Madiun City. The method used in this research is the qualitative method. By using interviews in collecting data. Based on the research that has been done, the researchers draw the conclusion that interpersonal communication carried out by frontline employees of the Ministry of Religion Affairs of Madiun City when providing services to prospective Hajj pilgrims is in accordance with the research focus, namely: Openness, Empathy, Supportiveness, Positiveness, and Equality.